Value relevance atas Informasi Akuntansi Sebelum dan Setelah Adopsi IFRS pada Sektor Keuangan - Fransisca Elsa Monica; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
The use of IFRS as an international accounting standard can provide benefits such as an increase of value relevance. However, there were still inconsistencies in previous research results regarding the influence of IFRS adoption on value relevance. Therefore, this study aimed to prove the influence of IFRS adoption on the value relevance of firm’s accounting information. The value relevance was measured by the association between accounting information in the form of earnings per share (EPS) and book value equity per share (BVPS) with stock price. The sample in this research consisted of 35 go public firms in the financial sector listed in the Indonesia Stock Exchange (IDX) in 2007-2014, with a sample of 280 observations. The analysis technique used was the panel data regression by using STATA software. This study was conducted by comparing the results of the analysis from the pre and post IFRS adoption period. The result showed an increase in value relevance in the post IFRS adoption period compared to pre IFRS adoption.